An ethnographic account of ecological consciousness: stories and daily practices of transformation and resistance - Ramírez, Anapaula (2018)
This article explores the relationship between humanity and nature, with the purpose of deepening our knowledge on how an ecological conscience is built. In this ethnographic study, conversations were held with three different persons who live in natural reserves in Ecuador, with the objective of exploring their life story and relating it to the territory they inhabit. These stories are framed in the theory of environmental ethics, the theory of the social actor, and the theory of practice, through which we analyze the motivations and transformations towards an ecological consciousness. The history of conservation in Ecuador is also described, making visible the various tools for conservation and their level of incidence in this country. Likewise, hotspots were identified worldwide and in Ecuador, to highlight the importance of private conservation, and finally define what is meant by ecological awareness. Through a qualitative-interpretative paradigm, and the use of methodological tools such as life stories, participant observation, and a field diary, the life of three conservation practitioners is analyzed in depth to identify motivations and practices that give account of an ecological consciousness.